Apprenticeship: The intention to quit and the role of secondary jobs in it - Katja Seidel (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2016)
This paper analyzes the effects of a secondary job on the intention to quit apprenticeship in Germany. For the empirical approach the representative German firmlevel study "BIBB Survey Vocational Training from the Trainees Point of View 2008" conducted by the Federal Institute for Vocational Education and Training is used. In this study 5901 apprentices were interviewed during their second year of apprenticeship. The probit regressions show a higher intention to quit if apprentices need a secondary job to cover their living costs.
Keywords: J22; J24; J38; 330; apprenticeship; dropout; quit; secondary job; income